Efficacy of erythritol powder air‐polishing in active and supportive periodontal therapy: A systematic review and meta‐analysis. Issue 1 (2nd August 2021) - Abdulbaqi, Hayder R.; Shaikh, Muhammad Saad; Abdulkareem, Ali A.; Zafar, Muhammad S.; Gul, Sarhang S.; Sha, Aram M.
Abstract: Objective: This systematic review aimed to analyse available evidence to answer two focused questions about the efficacy of erythritol powder air‐polishing (EPAP) (i) as an adjunctive during active periodontal therapy (APT) and (ii) as an alternative to hand/ultrasonic instrumentation during supportive periodontal therapy (SPT). Additionally, microbiological outcomes and patient's comfort/perceptions were assessed as secondary outcomes. Methods: PubMed, Cochrane and Medline were searched for relevant articles published before February 2021 following PRISMA guidelines. The search was conducted by three independent reviewers, and the agreement was measured by Cohen's kappa score. Out of 1043 articles, eight randomized clinical trials were selected for systematic review and quantitative synthesis. Only periodontal parameters, such as clinical attachment level (CAL), probing pocket depth (PPD) and bleeding on probing (BoP), showed homogeneity and, thus, were selected for meta‐analysis. Results: The improvement in PPD and BoP scores after using EPAP was comparable with hand/ultrasonic instrumentation during both APT and SPT. Significant CAL gain was achieved with EPAP during APT (0.16 mm, p < 0.02) compared with hand/ultrasonic instrumentation at the end point, whereas non‐significant CAL gain was achieved during SPT. No differences were observed regarding microbiological outcomes between the two treatment modalities. However, EPAP inflicted less pain and was better perceived by the patients. Conclusion: Erythritol powder air‐polishing can substitute hand/ultrasonic instrumentation for SPT, and CAL gain is significantly improved when EPAP is used as an adjunct during APT. For microbiological outcomes, no significant differences were observed between the two approaches; however, EPAP was better tolerated by the patients than hand/ultrasonic instrumentation. Clinical relevance: Erythritol powder air‐polishing can be used as an adjunct during APT and as an alternative to conventional mechanical debridement during SPT.